A novel allele, HLA‐DRB1*10:07 was identified in a Chinese individual. Issue 1 (14th May 2015) - He, J.‐J.; Zhang, W.; Wang, W.; He, J.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐DRB1*10:07 shows one nucleotide different from HLA‐DRB1*10:01:01 at position 328 in exon 2.